Analisis Pengendalian Mutu Konstruksi Pada Pelaksanaan Pembangunan Apartemen Sky House Alam Sutera+ Phase 2 - Fajriah, Dian Nurul; Lenggogeni, Lenggogeni; Yasinta, Rezi Berliana (Innovative: Journal Of Social Science Research, 2025)
Quality control in construction projects is a crucial factor to ensure the final product meets the established standards. This research analyzes the application of the quality control system in the construction project of Sky House Alam Sutera+ Phase 2. The study aims to identify whether quality control is implemented effectively, covering material inspection, laboratory testing, and on-site checks. Primary data was collected through interviews with quality control supervisors and field observations. The findings indicate that all quality control procedures were carried out systematically, with all test specimens meeting the required standards. Therefore, the implementation of quality control in this project successfully ensured the expected construction quality.